2017
DOI: 10.1039/c7cp02616a
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical behaviors of SiC(GeC)/MoS2 heterostructures: a first principles study

Abstract: Hybrid structures have attracted a great deal of attention because of their excellent properties, which can open up a way we could not foresee in materials science and device physics. Here, we investigate the electrical and optical behaviors of SiC(GeC)/MoS heterostructures, using first principles calculations based on density functional theory. Non-covalent bonding exists between the junctions due to the weak orbital coupling. Both junctions have optically active band gaps, smaller than that of the SiC or GeC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 46 publications
11
22
0
Order By: Relevance
“…All of the above elucidate these two heterostructures are all dynamically stable. The lattice constant of monolayer GeC is optimized to be a = 3.26 Å with hexagonal crystal structure, which accords well with previous results [24]. Monolayer GeC is similar to phosphorene, in which P atoms are substituted by Ge and C atoms alternately.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…All of the above elucidate these two heterostructures are all dynamically stable. The lattice constant of monolayer GeC is optimized to be a = 3.26 Å with hexagonal crystal structure, which accords well with previous results [24]. Monolayer GeC is similar to phosphorene, in which P atoms are substituted by Ge and C atoms alternately.…”
Section: Resultssupporting
confidence: 87%
“…This is mainly due to the positive transverse acoustic mode Grüneisen parameters. Rao et al [24] further calculated the electrical and optical behaviors of GeC/ MoS 2 heterostructure. Noncovalent bonding exists between the junctions due to the weak orbital coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In structural optimization process, the cell parameters are fixed while ionic positions are fully relaxed with k-point mesh of 5 Â 5 Â 1 generated based on Monkhorst and Pack scheme and 10 À5 eV energy convergence criteria. The optimized parameters including bond angles and atomic distances for stand-along BP/GeX meet well with previous results, ensuring the credibility of the above approach [24][25][26][27]. The above structures are further optimized until the forces on each atom are less than 0.01 eV/Å.…”
Section: Introductionsupporting
confidence: 71%
“…Shi et al studied the electronic properties of the GeC/WS 2 heterostructure under an electric field (E-field) and modulated its bandgap [26]. Rao et al studied SiC(GeC)/MoS 2 heterostructures and found enhanced optical absorption [27] and their results are promising for applications in field-effect transistors. To the best of our knowledge, the studies on the tunable electronic properties of heterostructures containing SiC and GeC are still lacking.…”
Section: Introductionmentioning
confidence: 99%